(untitled) (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2026)
Egg tofu is one of the foods that contains high protein because it is made from a mixture of soybeans and eggs. Eggs have complete nutritional content ranging from protein, fat, vitamins and minerals. This study aims to analyze the physical and organoleptic properties of egg tofu with the addition of various types of eggs, namely chicken eggs, free-range chicken eggs, duck eggs and IPB D1 chicken eggs. The analysis carried out included pH, water holding capacity (WHC), water absorption index (WAI), water solubility index (WSI), and Texture with an ANOVA test followed by Tukey and Duncan’s further test, and Organoleptic data were analyzed using the Kruskal–Wallis test. The results of the analysis showed that only the WHC value was significantly different (P <0.05) with the addition of various types of eggs. The use of varying egg types in egg tofu production did not reduce organoleptic quality, as it only affected overall appearance and color